The Effect of Public Expenditure and Economic Complexity on Income Disparity in Indonesia - Rachely, Balqys; Bashir, Abdul; Rohima, Siti (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2023)
Income distribution disparity is an economic issue addressed within the framework of the Sustainable Development Goals (SDGs), as it can have adverse effects on a country's socio-political landscape. This study aims to determine the impact of healthcare expenditure, educational expenditure, social spending, and trade on income distribution disparities in Indonesia. This research is of a quantitative nature, utilizing secondary data obtained from various sources, including the Directorate General of Fiscal Balance (DJPK) and the Central Bureau of Statistics (BPS). The analytical approach employed involves panel data regression analysis using the Random Effect Model (REM). The research scope encompasses all 34 provinces in Indonesia from 2010 to 2022. The findings reveal that both collectively and individually, healthcare expenditure, education expenditure, social protection spending, and trade significantly influence income distribution disparities in Indonesia. Specifically, investment in healthcare and education exhibits a negative correlation with income disparity, while social protection spending and trade displays a positive correlation.